Analisis penerapan akuntansi pertanggungjawaban sebagai alat penilaian kinerja pusat biaya pada Perusahaan Daerah Air Minum (PDAM) Kabupaten Tana Toraja - Pala’langan , Eri Novayanti; Saerang, David Paul Elia; Tirayoh, Victorina Z. (Manajemen Bisnis dan Keuangan Korporat, 2024)
Responsibility accounting is a system that is arranged in such a way according to the nature and activities of the company with the aim that each organizational unit can be accountable for the results of the activities of the unit under its supervision and can be used by the company to assess the performance of managers, especially the cost center. The application of accountability accounting can be said to be good if the conditions of its application are met. The requirements of accountability accounting are organizational structure, budget preparation, classification of controlled and uncontrolled costs, classification of account codes, and accountability reports. The purpose of this study was to determine the application of responsibility accounting in assessing the performance of the cost center at the Regional Drinking Water Company (PDAM) of Tana Toraja Regency. The analysis method used in this research is descriptive method which aims to describe the data that has been collected as it is obtained from the results of interviews and data collected from the company. Based on the results of the study, it shows that the application of accountability accounting in the performance assessment of the cost center at the Regional Drinking Water Company (PDAM) of Tana Toraja Regency is not good enough, because in the company's accountability report there are still costs that are combined into one account that should be classified. The company has also not implemented a clear and firm reward and punishment system.